Positron emission tomography-guided therapy of aggressive Non-Hodgkin Lymphomas (PETAL): a multicenter, randomized phase III trial - Dührsen, Ulrich; Haberkorn, Uwe (Journal of clinical oncology, 2018)
PurposeInterim positron emission tomography (PET) using the tracer, [18F]fluorodeoxyglucose, may predict outcomes in patients with aggressive non-Hodgkin lymphomas. We assessed whether PET can guide therapy in patients who are treated with cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP).Patients and MethodsNewly diagnosed patients received two cycles of CHOP—plus rituximab (R-CHOP) in CD20-positive lymphomas—followed by a PET scan that was evaluated using the ΔSUVmax method. PET-positive patients were randomly assigned to receive six additional cycles of R-CHOP or six blocks of an intensive Burkitt’s lymphoma protocol. PET-negative patients with CD20-positive lymphomas were randomly assigned or allocated to receive four additional cycles of R-CHOP or the same treatment with two additional doses rituximab. The primary end point was event-free survival time as assessed by log-rank test.ResultsInterim PET was positive in 108 (12.5%) and negative in 754 (87.5%) of 862 patients treated, with statistically significant differences in event-free survival and overall survival. Among PET-positive patients, 52 were randomly assigned to R-CHOP and 56 to the Burkitt protocol, with 2-year event-free survival rates of 42.0% (95% CI, 28.2% to 55.2%) and 31.6% (95% CI, 19.3% to 44.6%), respectively (hazard ratio, 1.501 [95% CI, 0.896 to 2.514]; P = .1229). The Burkitt protocol produced significantly more toxicity. Of 754 PET-negative patients, 255 underwent random assignment (129 to R-CHOP and 126 to R-CHOP with additional rituximab). Event-free survival rates were 76.4% (95% CI, 68.0% to 82.8%) and 73.5% (95% CI, 64.8% to 80.4%), respectively (hazard ratio, 1.048 [95% CI, 0.684 to 1.606]; P = .8305). Outcome prediction by PET was independent of the International Prognostic Index. Results in diffuse large B-cell lymphoma were similar to those in the total group.ConclusionInterim PET predicted survival in patients with aggressive lymphomas treated with R-CHOP. PET-based treatment intensification did not improve outcome.
Gesehen am 25.06.2019